A Crystalline, 2D Polyarylimide Cathode for Ultrastable and Ultrafast Li Storage. Issue 28 (17th May 2019) - Wang, Gang; Chandrasekhar, Naisa; Biswal, Bishnu P.; Becker, Daniel; Paasch, Silvia; Brunner, Eike; Addicoat, Matthew; Yu, Minghao; Berger, Reinhard; Feng, Xinliang
Abstract: Organic electrode materials are of long‐standing interest for next‐generation sustainable lithium‐ion batteries (LIBs). As a promising cathode candidate, imide compounds have attracted extensive attention due to their low cost, high theoretical capacity, high working voltage, and fast redox reaction. However, the redox active site utilization of imide electrodes remains challenging for them to fulfill their potential applications. Herein, the synthesis of a highly stable, crystalline 2D polyarylimide (2D‐PAI) integrated with carbon nanotube (CNT) is demonstrated for the use as cathode material in LIBs. The synthesized polyarylimide hybrid (2D‐PAI@CNT) is featured with abundant π‐conjugated redox‐active naphthalene diimide units, a robust cyclic imide linkage, high surface area, and well‐defined accessible pores, which render the efficient utilization of redox active sites (82.9%), excellent structural stability, and fast ion diffusion. As a consequence, high rate capability and ultrastable cycle stability (100% capacity retention after 8000 cycles) are achieved in the 2D‐PAI@CNT cathode, which far exceeds the state‐of‐the‐art polyimide electrodes. This work may inspire the development of novel organic electrodes for sustainable and durable rechargeable batteries. Abstract : Crystalline 2D polyarylimide integrated with carbon nanotube (2D‐PAI@CNT) is prepared via in situ synthesis and is explored as the cathode for Li‐ion batteries. The abundant redox active sites, the robust framework made from imide cores/cyclic linkage, and the well‐defined porous structure endow 2D‐PAI@CNT with ultrastable cycling stability and excellent rate capability to store Li charges, outperforming state‐of‐the‐art polyimide cathodes for rechargeable batteries.